From Clinical Signs to Functional Recovery: A Practice-Oriented Review of Rotator Cuff Tear Management in Primary Care - Jakub Piotr Adamus; Kacper Dywan; Zuzanna Paszt; Julia Dąbrowska; Michal J. Tracz; Paweł Łęgosz; Sławomir Struzik (Journal of Clinical Medicine, 2026)
Rotator cuff tear (RCT) is a leading cause of shoulder pain encountered by general practitioners. Population-based screening shows that nearly half of full-thickness tears are asymptomatic, allowing many lesions to progress undetected. This narrative review summarises 105 clinical, imaging, biomechanical and rehabilitation studies published in recent years. The review follows the disorder from early tendinopathy to full-thickness tear and discusses crucial risk factors (age, diabetes, hypercholesterolaemia, overhead work). It aims to guide early primary-care management of RCT. We examine the diagnostic accuracy of classic bedside tests, including the supraspinatus weakness and external rotation lag cluster. Furthermore, we explain when ultrasound or MRI adds value and what the classic findings are. An informative overview of patient-reported outcome tools (e.g., SPADI, WOSI, Constant–Murley, ASES) could help physicians select one for follow-up. The article objectively evaluates the evidence for conservative measures—structured exercise protocols, manual therapy, oral analgesics, and corticosteroid or platelet-rich plasma injections. Moreover, we propose an evidence-based postoperative rehabilitation timeline with milestones that incorporate targeted immobilisation and progressive loading. The article presents selected clinical situations, such as the impact of type 2 diabetes on tendon biology. We explore the viability of experimental adjuncts such as extracorporeal shock-wave therapy, low-intensity pulsed ultrasound and electrical stimulation. Finally, we compare recommendations from the American Academy of Orthopaedic Surgeons and the European Society for Surgery of the Shoulder and Elbow. We highlight similarities between the recommendations (e.g., overlapping clinical examination tests), thereby facilitating their clinical application and providing a pragmatic guide for general practitioners. Our synthesis draws on orthopaedic, radiographic and rehabilitation data to reduce diagnostic delay, optimise non-specialist resource use, and improve pain and functional outcomes for the growing population affected by rotator cuff tears.